2023
DOI: 10.1039/d2ce01578a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structures and magnetic properties of the Eu-based quaternary tellurides EuGdCuTe3and EuLuCuTe3

Abstract: Novel paramagnetic tellurides EuGdCuTe3 and EuLuCuTe3, with the transition to a ferrimagnetic state at ∼8 K and ferromagnetic state at ∼3 K, respectively, are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…When comparing the structural parameters of the EuErCuTe 3 compound with the already known europium tellurides EuGdCuTe 3 and EuLuCuTe 3 [42], their decrease was observed with a decrease in the ionic radius of Ln 3+ (r i (Gd 3+ ) = 0.938 Å > r i (Er 3+ ) = 0.89 Å > r i (Lu 3+ ) = 0.861 Å) [26]. The unit cell parameters of EuLnCuTe 3 (Ln = Gd [42], Er (Table 1), Lu) [42] changed as follows:…”
Section: Crystal Structures Of the Euercutementioning
confidence: 99%
“…When comparing the structural parameters of the EuErCuTe 3 compound with the already known europium tellurides EuGdCuTe 3 and EuLuCuTe 3 [42], their decrease was observed with a decrease in the ionic radius of Ln 3+ (r i (Gd 3+ ) = 0.938 Å > r i (Er 3+ ) = 0.89 Å > r i (Lu 3+ ) = 0.861 Å) [26]. The unit cell parameters of EuLnCuTe 3 (Ln = Gd [42], Er (Table 1), Lu) [42] changed as follows:…”
Section: Crystal Structures Of the Euercutementioning
confidence: 99%
“… 7 19 For quaternary europium chalcogenides EuLnCuCh 3 (Ch = S, Se), it has been suggested that if the magnetic moment of the Ln 3+ ion is significantly less than the magnetic moment of the Eu 2+ ion, the compound will be ferromagnetic, and if the magnetic moment of the Ln 3+ ion is equal to or greater than that of the ion Eu 2+ , the compound exhibits ferrimagnetic properties. 20 24 Chalcogenides EuLnCuCh 3 (Ch = S, Se, Te), containing nonmagnetic ions Ln 3+ = La 3+ , Y 3+ , Lu 3+ and Sc 3+ , exhibit exclusively ferromagnetic ordering of the Eu 2+ moments with the ground state 8S 7/2 at 2.4–6.4 K. 12 , 13 , 20 , 22 , 23 However, chalcogenides with magnetic ions Ln 3+ = Ce 3+ –Sm 3+ and Gd 3+ –Yb 3+ exhibit both ferro- and ferrimagnetic behavior at 1.7–4.3 K and 4.5–6.2 K, respectively. 12 , 13 , 20 22 , 25 In the L- 12 and N-type ferrimagnets, according to the Néel classification, 26 the effect of negative magnetization was discovered.…”
Section: Introductionmentioning
confidence: 99%